Targeting HER2-positive gastric cancer with a novel 18F-labeled ZHER2:342 probe. Issue 19 (8th April 2019) - Pan, Yunyun; Yang, Zhengyang; Xu, Yuping; Bai, Zhicheng; Pan, Donghui; Yang, Runlin; Wang, Lizhen; Guan, Wenxian; Yang, Min
Abstract : Tumor targeting of the novel 18 F-labeled ZHER2:342 probe in HER2-positive gastric cancer xenograft models. Abstract : To realize the diagnosis of HER2-positive gastric cancer via PET imaging, herein, a new kind of 18 F-labeled HER2 affibody probe was created; the bifunctional maleimide derivative 1, 4, 7-triazacyclononane-1, 4, 7-triacetic acid (NOTA-MAL) was first coupled to a polypeptide, and the resulting compound was subsequently labeled with the 18 FAl complex. The binding characteristics of the probe were assessed using both in vitro studies and in vivo microPET imaging and biodistribution experiments. Immunohistochemical staining was performed to confirm the expression level of HER2 in the studied cell lines and tumors. The probe was successfully produced with the radiochemical purity of more than 95%. The NCI N87 cell-associated radioactivity was 19.31 ± 1.01% AD, and it decreased to 0.83 ± 0.04% AD per 10 6 cells after blocking HER2 as early as 15 minutes post-incubation ( p < 0.05). A competition binding assay between radiolabeled and non-radioactive affibody molecules with NCI N87 indicated that the IC50 was 8.10 nM. The microPET imaging and biodistribution of human gastric cancer xenografts demonstrated that the probe could specifically accumulate in tumors at early time points. Protein detection confirmed a strong HER2 expression in NCIN87 and a weak HER2 expression in SGC7901. In conclusion, 18 FAl-NOTA-MAL-Cys-GGGRDN(M 0 )-ZHER2:342 was successfully prepared via a one-step method. The favorable preclinical data showed specific and effective tumor targeting capacity of the proposed probe; this revealed that the probe proposed herein might have potential application in gastric cancer imaging.